Effect of Constraint-Induced Movement Therapy on Motor Function of Rats with Cerebral Ischemia-Reperfusion Injury Based on Magnetic Resonance Spectroscopy Imaging - JIANG Pingli; CHEN Xiaocheng; XU Wenshan; DING Yanyi; LIU Weilin; TAO Jing (康复学报)
ObjectiveAnimal magnetic resonance spectroscopy (MRS) imaging was used to detect the level of glutamate and γ-aminobutyric acid in motor cortex of rats, and to explore the regulatory effect of constraint-induced movement therapy (CIMT) on motor function of rats with cerebral ischemia-reperfusion injury.MethodsThe modified Longa suture method was used to construct the left middle cerebral artery occlusion reperfusion injury rats model (MCAO). After modeling, the rats were randomly divided to the control group and the CIMT group, with six rats in each group. The rats moved freely in the cage in the control group; CIMT intervention was performed in the CIMT group after modeling at the 7th day, the rat's healthy side was immobilized, and the affected side was forced to move during the CIMT intervention, 20 minutes a day, continuous intervention for two weeks. Before and after CIMT intervention, the open field test was used to evaluate the motor function; the modified neurological severity score (mNSS) was used to evaluate the neurological deficits; 9.4 T small animal nuclear magnetic resonance (MRS) imaging was used to detect the changes of glutamate and γ-aminobutyric acid levels in the bilateral motor cortex of rats.Results① Open field test results：compared with the control group, the total distance of exercise in the CIMT group after intervention for two weeks was significantly increased, the difference was statistically significant (P<0.05). ② mNSS score results: compared with the control group, the mNSS score of the CIMT group after intervention for two weeks was significantly decreased, the difference was statistically significant (P<0.05). ③ Comparison of glutamate and γ-aminobutyric acid levels in the M1 area of the motor cortex: compared with before intervention, the ratio of glutamate/creatinine in the M1 area of the healthy side motor cortex was significantly decreased, and the glutamate/creatinine ratio in the M1 area of the affected side motor cortex of rats in the CIMT group was significantly increased, γ-aminobutyric acid/creatinine ratio was significantly was significantly decreased (P<0.05). Compared with the control group, the ratio of glutamate/creatinine in the M1 area of the affected lateral motor cortex in the CIMT group was significantly increased, and γ-aminobutyric acid/creatinine ratio was significantly decreased (P<0.05).ConclusionCIMT can improve motor dysfunction and neurological deficit of rats with cerebral ischemia-reperfusion injury, and its mechanism may be related to increasing the level of excitatory neurotransmitter glutamate in M1 area of motor cortex and reducing inhibitory neurotransmitter γ- aminobutyric acid level.